Growth response of Kampung and Pelung cross chickens to diet differed in protein content - Iskandar, Sofjan; Z, Desmayati; Sastrodihardi, S; Sartika, T; Setiadi, P; Susanti, T (Indonesian Journal of Animal and Veterinary Sciences, 1998)
Two lines of native chicken (Kampung and Pelung cross) were subjected to diets differed in protein content (21, 19, 17and 15%), but isocaloric (2,900 kcal ME/kg). Ten (5 males, 5 females) day old chicks were allocated as replicate and thetreatments were 2 lines x 4 levels dietary protein. The trial was conducted for 12 weeks period . Bodyweight gain of Kampungchicken (704 g/bird) was lower than ofPelung cross chicken (844 g/bird). Based on bodyweight gain and feed conversion ratio,the optimum level of dietary crude protein was 19% for both lines, whilst consumption was not affected either by lines nor bydietary protein. Pelung cross chicken converted feed to body weight more efficiently than Kampung chicken did. However feedconversion ratio increased with decreasing in dietary protein. Mortality was not affected either by lines nor by dietary protein.Twelve weeks carcass percentage of Pelung cross (64,9%) was higher than of Kampung chickens (62,9%), however carcass percentage was not affected by the dietary protein. Abdominal fat pad was not affected by lines of chickens nor dietary protein. Â  Key words : Native chicken, protein, growth, carcass